2018
DOI: 10.1021/acs.orglett.8b03876
|View full text |Cite
|
Sign up to set email alerts
|

Sulfite-Promoted Synthesis of N-Difluoromethylthioureas via the Reaction of Azoles with Bromodifluoroacetate and Elemental Sulfur

Abstract: A sulfite-promoted transformation of azoles into Ndifluoromethylthioureas through N-difluoromethylation and sulfuration has been developed. In this reaction, inexpensive ethyl bromodifluoroacetate and nontoxic elemental sulfur were used as the difluoromethylation and sulfuration reagents, respectively. A variety of azoles, including benzimidazoles, imidazoles, and triazoles, performed well to afford a broad range of azole thioureas in moderate to good yields.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 44 publications
0
26
0
Order By: Relevance
“…Quite recently, Tang's group has synthesized N‐ difluoromethylthiourea derivatives 95 using the reaction of azoles 93 with bromodifluoroacetate 94 and rongalite (Scheme ) . In their study, they have tried diverse sulfite reagents for dehalogenation reaction but they observed that rongalite gave better yields in the presence of dimethylacetamide (DMA) solvent at 100 °C.…”
Section: Applications Of Rongalite Chemistry In Organic Synthesismentioning
confidence: 99%
“…Quite recently, Tang's group has synthesized N‐ difluoromethylthiourea derivatives 95 using the reaction of azoles 93 with bromodifluoroacetate 94 and rongalite (Scheme ) . In their study, they have tried diverse sulfite reagents for dehalogenation reaction but they observed that rongalite gave better yields in the presence of dimethylacetamide (DMA) solvent at 100 °C.…”
Section: Applications Of Rongalite Chemistry In Organic Synthesismentioning
confidence: 99%
“…Tang and Li presented a new methodology for the transformation of azoles into N-difluoromethylated thioureas using elemental sulfur, BrCF 2 CO 2 Et as a CF 2 H source and the sulfite salt HOCH 2 SO 2 Na in DMA at 100 °C (Scheme 23, C). 84 The reaction was compatible with a variety of substituted imidazoles, benzimidazoles and triazoles to furnish the corresponding difluoromethyl thiourea products in yields ranging from 13-88%. The corresponding difluoromethyl selenoureas were prepared in the presence of selenium instead of sulfur under the same reaction conditions.…”
Section: Short Review Syn Thesismentioning
confidence: 92%
“…The Tang group reported a unique transformation leading to N-difluoromethylated thioureas from azoles (Scheme 55A). 199 To successfully prepare these products, the authors reacted…”
Section: N-difluoromethylationmentioning
confidence: 99%